What is Wrong with Democracy? A View from Hizbut Tahrir - Hasbi Aswar (Department of International Relations, Brawijaya University, 2017)
By the end of the cold war era, democracy is believed as the last solution of the world problem. Democracy is believed can solved political, economic and social problems. Fundamental principles of democracy as people participating in politics, transparent system of government, limitations on the power of governments and protection of human rights is perceived as the only solution of the human problem. In muslim world, democracy is responded differently. Some say, democracy is compatible with Islam, what democracy struggle for is similar with the mission of Islam. However, another perspective to say, Islam contrasts with democracy. Democracy is derived from western and secular values while Islam is from god revelation and every Muslim should be bound by Islamic Law. This paper will describe the argument of Hizbut Tahrir for its objection to democracy. Hizbut Tahrir is an international group that always calls for establishing world state system under Islamic Law called Khilafah. Khilafah, according to Hizbut Tahrir, is the only state political system that is legalized by Islam and derived from Quran and Sunnah (prophetic tradition). The opposition of Hizbut Tahrir toward democracy here can be seen in two aspects. Firstly, the difference of the notion sovereignty, god or human sovereignty. Secondly, the standardization of freedom of the people based on consensus or god law. Western intellectuals and think tanks include Hizbut Tahrir as one of radical and fundamentalist group.Keyword: Democracy, Hizbut Tahrir, Khilafah, Fundamentalist Group